COMPETITIVE DESTINATION PADA WISATA URBAN DAN WISATA RURAL - Dhanik Puspita Sari; Pepen Gustamiaji (Bogor Hospitality Journal, 2020)
The destination or tourist destination that is intended by tourists, certainly has several criteria or attributes of comparison used as a consideration material for tourists to come and spend time somewhere they are going. Bandung city and the Bogor City are two cities located in the province of West Java which has lot of urban tourist destinations. Similarly, Sindang Barang Cultural Village located in Bogor city with Saung Angkung Udjo in Bandung city as a rural tourism. The method used is a qualitative method by reviewing the secondary data that exists by using the checklist sheet as its research tool. The results showed that Bandung has a better competitive level as an urban tourist destination compared to Bogor. As for rural tourism, Saung Angklung Udjo is more competitive when compared to Sindang Barang Cultural Village located in Bogor city.